A Possibility of Increasing Audit Coverage to Gain Voluntary Compliance - Gunadi Gunadi (LPPM-STPI, 2020)
One element of this jurisdiction is revenue jurisdiction, under which a State may legally require part of her people’s resources (income and wealth) to meet her expenditures (Knechtle, 1979). Meanwhile, Le Contract Social (introduced by Rousseau, from Safri Nurmantu, 2003) states that people are oblige to share their resources to their State to meet expenditures for collective interests. Therefore, these theories view that tax from the people’s side is a socio-legal obligation, whereas from the State’s side is her socio-legal rights to share parts of the people’s income and wealth as a support to the state’s revenues.